Colectividades territoriales y globalización: contribuciones para una nueva acción estratégica de emancipación - Ferrí£o, Joí£o (Revista EURE - Revista de Estudios Urbano Regionales, 1995)
Motivated by a growing dissatisfaction with regional policies and with the currently predominant concept of regional development, this text explores new paths towards: 1) Incorporating regional development within a broader view of strategic action for territorial emancipation, and 2) guiding this effort by the principles of sustainable development. An analytical method, structured on three core interests (state, market and civilian society), is proposed. The main forms of intervention, which must comply with the strategies of territorial development, are identified and, finally, some proposals are made which aim to consolidate a new explicit regional development policy.